AJI JANANTAKA: PEMAHAMAN TEOLOGI SOSIAL DAN EKOLOGI TUMBUHAN - Ni Wayan Winiantari (Jnanasidanta, 2021)
Lontar Aji Janantaka is a speech that describes the types of trees and flower plants that get grace after being hit by a disease outbreak. Aji Janantaka describes the special functions of trees according to their types. Aji Janantaka explained that one of the real aspects is a holistic understanding for the community about tree planting according to its benefits and uses. The plant species described in Aji Janantaka are distinguished based on the position of the population, community and plant ecosystem, which is related to theology. The method used in this article is a literature study, by examining books, similar scientific articles, and references related to Aji Janantaka's plants and lontar. Aji Janantaka explained the classification of plants based on the position of plants and the benefits of plants with the aim of providing knowledge as a basis for humans to use plants in everyday life both as building materials and also as a means to support ceremonies and ceremonies. Classification of plant species based on the position of plants when they are still humans which then grow into various types of plants that can be used as building materials and cannot be used as building materials. Classification of plant species based on the grace given by Bhatara Sakti Wawu Rauh to plant species including fragrant trees. Lontar Aji Janantaka also explained the classification of plants classified as fragrant based on the grace given by Ida Bhatara Sakti Wawu Rawuh. Keywords: Ecology, Plant,  Aji Janantaka